CHEMICAL AND PHYSICAL ATTRIBUTES OF SOIL, AND CARBON AND NITROGEN STOCK AND HUMIC FRACTIONS IN DIFFERENT PLANT FORMATIONS - Giacomo, Romulo Guimaraes [UNESP]; Pereira, Marcos Gervasio; Guareschi, Roni Fernandes; Machado, Deivid Lopes [UNESP] (Centro Pesquisas Florestais, Ufsm, 2015)
Cerrado biome is the second largest Brazilian biome, where different phyto-physiognomical features are observed, which may be influenced by soil factors. Thus, this study aimed to evaluate soil physical and fertility properties (particle size analysis, bulk density - BD and total pore volume - TPV), carbon and nitrogen stocks and chemical fractions of soil organic matter (SOM) in areas of mesophytic forest, Cerrado and Cerrado sensu stricto in the ecological station of Pirapitinga, Minas Gerais state. The soil was classified as Oxisol and soil samples were collected from the layers 0-0.05, 0.05-0.1, 0.1-0.2, and 0.2-0.4 m. The experimental design was completely randomized. Areas of mesophytic forest and cerrado grow in soil with higher clay compared to the Cerrado sensu stricto, indicating that possibly more clayey soils have higher water holding capacity and nutrient supply to attend the demand more appropriately with larger vegetations. The mesophytic forest area by presenting high waste disposal of plant and be in the clayey soil is in some layers providing higher levels of soil organic C and humic substances, triggering lower values of bulk density, greater total porosity and availability of P in relation to other vegetation types studied. However, the closed areas and Cerrado sensu stricto have higher amounts of Mg, K, and lower pH, H + Al and Al compared to mesophitic forest area, which may suggest that these phytophysiognomies settle preferentially in the most fertile soils of Cerrado biome. The relationship between the humic acid and fulvic acid fraction indicates that the forest vegetation Mesophytic presents for vegetation of Cerrado and Cerrado sensu stricto soil organic matter of great quality, which allows the establishment of physical and chemical attributes favorable to the development of the plant. The largest stocks of carbon are verified in larger vegetation, cerrado and mesophytic forest. However, the higher grade and stock soil nitrogen occur in Cerrado sensu stricto.
Keywords: Physiognomies of Cerrado biome; soil fertility; organic matter